2013
DOI: 10.1007/s00221-013-3513-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of motor imagery and peripheral nerve electrical stimulation on the motor cortex

Abstract: Although motor imagery enhances the excitability of the corticospinal tract, there are no peripheral afferent inputs during motor imagery. In contrast, peripheral nerve electrical stimulation (ES) can induce peripheral afferent inputs; thus, a combination of motor imagery and ES may enhance the excitability of the corticospinal tract compared with motor imagery alone. Moreover, the level of stimulation intensity may also be related to the modulation of the excitability of the corticospinal tract during motor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…During the shortening contraction task, low-intensity electrical nerve stimulation increased the excitability of the corticospinal tract, but high-intensity electrical nerve stimulation did not. This is consistent with the results found in our previous study, in which the effect of electrical stimulation on corticospinal excitability was dependent on stimulus intensity ( Saito et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…During the shortening contraction task, low-intensity electrical nerve stimulation increased the excitability of the corticospinal tract, but high-intensity electrical nerve stimulation did not. This is consistent with the results found in our previous study, in which the effect of electrical stimulation on corticospinal excitability was dependent on stimulus intensity ( Saito et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…The stimulation intensity was effective in modulating the change in corticospinal excitability by electrical stimulation with voluntary movement. When the stimulated muscle is voluntarily shortened, low-intensity electrical stimulation displays significantly increased corticospinal excitability than high-intensity electrical stimulation ( Saito et al, 2013 ). However, the effect of stimulation intensity on corticospinal excitability is considered to depend on whether or not the stimulated muscle is active.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important source of variability in the effects of neurostimulation is brain-state dependency, i.e., the effect of neurostimulation depends on the timing of stimulation with respect to the underlying brain state. A number of studies have shown that applying neurostimulation in a brain-state dependent manner can enhance the modulation of corticospinal excitability (Kraus et al 2016;Kaneko et al 2014;Saito et al 2013). Ultimately, taking into account these factors in the application of neurostimulation should lead to a more personalized and adaptive neuromodulatory therapy to reduce chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of such studies contribute to the refining of future experimental paradigms in RCTs (Dobkin, 2009). For patients with difficulty in engaging in MI, the enhancing effects of brain stimulation, such as Transcranial Direct Current Stimulation (Ang et al, 2012; Foerster et al, 2013) or peripheral stimulation (Saito et al, 2013), on MI may prove to be useful. We also need to examine more closely the brain changes associated with MI training and also to characterize the effects of different modes of MI delivery using neuroimaging methodology such as Near Infrared Spectroscopy (NIRS) that is more amenable to recording changes in brain function during functional activities (Mihara et al, 2013).…”
Section: Future Research Targetsmentioning
confidence: 99%